Artziny jako medium (dla) sztuki - Lachman, Magdalena; Polit, Paweł ((Dy)fuzje: Związki literatury i sztuki w Polsce po 1945 roku, 2019)
The article analyses a variety of meanings and semantic contexts of ‘artzin’. In its regular sense, the concept refers to independent, often irregular, publications which are published outside of the mainstream circulation. Artzins are often an expression of a variety of subcultures. The article also considers the possibility of using this term to name a number of publications authored by established visual artists which are sometimes similar to newspaper form. The article proposes to call them ‘press art’. Such creations are rooted in early twentieth century avant-garde and connected with the mechanical reproduction of artworks in later decades of the previous century. They also exhibit the energy of artistic happening. For many artists such publications open a possibility of exploring the nature of the medium through which they work, which is both a challenge and a possibility.